One-Tier versus Two-Tier Wireless Sensor Networks: Coverage Problem - Tarek Sheltami (International Journal of Distributed Sensor Networks)
This paper tackles the coverage problem in homogenous and heterogeneous wireless sensor networks. The homogenous sensor network consists of sensor nodes and relays; however, the heterogeneous sensor network consists of sensor nodes, super nodes, and satellite nodes. In the latter network, super nodes and satellite nodes are utilized to demonstrate different scenarios. Super nodes consume huge amount of energy, compared to sensor nodes. To address this problem, the aim of this paper is to find the baseline when super nodes are used efficiently, despite the inherited high power consumption. Wolfram Mathematica is used to compare random independent deployment circular analytical model against a much simpler square analytical model. The achieved results showed that the simple square model is very close to circular model when K -coverage is ≤2.